Media Representations of Jesus Christ: The Dichotomy between the Sacred and the Profane - Vitkūnė-Bajorinienė, Aistė; Gabrėnaitė, Eglė (Verbum, 2025)
Today, images of Christ are used in visual media to create new meanings. This article aims to determine the relationship between the sacred and the profane as reflected in the images of Jesus on the front covers of popular magazines. In 2023, a study of around 12,000 magazine covers from 2001 to 2023 was conducted, focusing on 80 of the most popular periodical publications globally. Forty-two covers were found to include visual references to Jesus Christ and were examined using the social semiotic approach and rhetorical discourse analysis. The research confirmed that the publishing industry follows a relatively consistent policy of exploiting the image of Jesus. It can be concluded that sacral elements in the studied images tended to dominate over secular aspects. Also, the analysis confirmed that the cover images of Jesus reflect current historical, religious, and cultural contexts and accommodate the diversity of viewpoints.